ANALISIS FRAMING PEMBERITAAN PERTIKAIAN KELOMPOK MAHASISWA TIMUR, NTT, MALUKU, DAN PAPUA DI YOGYAKARTA OLEH MOJOK.CO DAN KOMPAS.COM - Hussein, Bill; Rachma Dewi, Putri Aisyiyah (The Commercium, 2023)
This research explains the media framing of the news of the clashes between NTT, Maluku and Papua students that occurred in Yogyakarta, precisely in the Babarsari area by Mojok.co and Kompas.com in 2022. To achieve the above objectives, a qualitative research method is used with Robert Entmen’s framing analysis research type. Where in Robert Entmen’s theory. The analysis in this study uses four elements of Robert Entmen’s framing analysis, namely defining the problem, estimating the source of the problem, making moral decisions, and emphasizing solutions. Which is then analyzed through the process of data collection, data reduction, data presentation, and conclusion drawing. The presentation of data in this study is in the form of writing and explaining what it is according to the data in the field.